TELAAH SUBSEKTOR INDUSTRI KECIL DAN MENENGAH (IKM) UNGGULAN KABUPATEN BANTUL, 2005-2012 - , SEPTIAN THAHIR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to identify leading subsectors of small and medium enterprises (SME) and their potential in Bantul Regency period 2005-2012. The leading subsectors of SME are analysed with both comparative and competitive advantages. The data used are total labour of SME subsectors from the Department of Industry, Trade, and Cooperation in Yogyakarta Province. Static Location Quotient (SLQ) is used to analyse the comparative advantages of SME subsector and Dynamic Location Quotient (DLQ) is used to analyse the potential of comparative advantages of SME subsector. A Shift Share Analysis consists of Classic and Arcelus is used to analyse of competitive advantages of SME subsector and Overlay Analysis is used to analyse the potential of competitive advantages. The results demonstrate that the âSME Crafts Subsectorâ is the leading subsectors of SME which has potential leading both competitive and comparative in Bantul Regency. In addition, âSME Chemical and Constructions Materialsâ also has potential comparative advantages, but this subsector doesnât have the potential for competitive advantages. Whereas, for the other subsectors of SME in Bantul Regency such as âfoodâ, âcloths and leatherâ, and âmetal and electronicsâ donât have any advantages, either comparative or competitive.